2021
DOI: 10.1037/sah0000271
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between social support and experienced and internalized HIV-related stigma among people living with HIV in the Deep South.

Abstract: The Deep South has experienced disproportionately high HIV diagnosis and death rates compared to other U.S. regions. Stigma experiences and perceptions are particularly high among individuals living with HIV in the Deep South and are consistently associated with negative health outcomes including poorer medication adherence. This study included a survey of 201 individuals living with HIV in the Deep South and examined the relationship between social support and internalized stigma with a focus on individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…Disentangling how various forms of stigma work to impact quality-of-life outcomes across psychological, social, and health dimensions, and whether social support can buffer against the internalization of public stigma is not only theoretically important, it is important for the design of effective interventions that reduce stigma and improve quality of life in PLHIV. 5 , 36 …”
Section: Introductionmentioning
confidence: 99%
“…Disentangling how various forms of stigma work to impact quality-of-life outcomes across psychological, social, and health dimensions, and whether social support can buffer against the internalization of public stigma is not only theoretically important, it is important for the design of effective interventions that reduce stigma and improve quality of life in PLHIV. 5 , 36 …”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that social support is extremely important in deterring the negative consequences for people who face disease stigma (e.g., Reif et al, 2021). People who contract COVID-19 because they failed to follow public health protocol might experience reduced instrumental, emotional, and social support from people in their immediate circle (e.g., Johnson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…During the past two decades, numerous reviews (systematic reviews, scoping reviews, literature reviews) have examined HIV stigma reduction interventions (Brown et al, 2003;Dunbar et al, 2020;Ingram et al, 2019;Kane et al, 2019;Kemp et al, 2019;Ma et al, 2019;Mahajan et al, 2008;Mak et al, 2017;Pantelic et al, 2019;Rao et al, 2019;Reif et al, (Reif et al, 2015). From an ecological perspective, these interventions can be organized as (a) individual level only, (b) at the individual and relational level, (c) at the individual and structural level, and (d) at the structural level only (Pantelic et al, 2019).…”
Section: Overview Of Hiv-related Stigma Interventionsmentioning
confidence: 99%
“…First, HIV-related stigma intervention research needs to use a longitudinal design (Brown et al, 2003;Kane et al, 2019;Reif et al, 2015). Without a longitudinal design, the ability to identify the efficacy of an HIV-related stigma intervention on distal care continuum outcomes (adherence, engagement in care) is limited.…”
Section: Specific Priorities For Future Hiv-related Stigma Researchmentioning
confidence: 99%
See 1 more Smart Citation